2006
DOI: 10.1515/bc.2006.062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of trypsin I as a candidate for influenza A virus and Sendai virus envelope glycoprotein processing protease in rat brain

Abstract: Extracellular cleavage of virus envelope fusion glycoprotein hemagglutinin (HA0) by host trypsin-like proteases is a prerequisite for the infectivity and pathogenicity of human influenza A viruses and Sendai virus. The common epidemic influenza A viruses are pneumotropic, but occasionally cause encephalopathy or encephalitis, although the HA0 processing enzyme in the brain has not been identified. In searching for the brain processing proteases, we identified a processing enzyme in rat brain that was inducible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…This sparing effect is probably related to the protective role of the blood-brain barrier against the transport of pathogenic molecules into the brain. However, trypsin in the brain is distributed mainly in cerebrovascular endothelial cells and hippocampal neuronal cells [12], [38], and it is up-regulated in vascular endothelial cells by proinflammatory cytokines in the blood [7]. These findings suggest that the high levels of proinflammatory cytokines in the blood after IAV infection induce trypsin in cerebrovascular endothelial cells and DADA may suppress trypsin levels in the brain through down-regulation of cytokines.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This sparing effect is probably related to the protective role of the blood-brain barrier against the transport of pathogenic molecules into the brain. However, trypsin in the brain is distributed mainly in cerebrovascular endothelial cells and hippocampal neuronal cells [12], [38], and it is up-regulated in vascular endothelial cells by proinflammatory cytokines in the blood [7]. These findings suggest that the high levels of proinflammatory cytokines in the blood after IAV infection induce trypsin in cerebrovascular endothelial cells and DADA may suppress trypsin levels in the brain through down-regulation of cytokines.…”
Section: Discussionmentioning
confidence: 90%
“…Since the levels of proinflammatory cytokines are closely interconnected to those of trypsin and influenza virus replication rate in target organs through the influenza virus–cytokine–trypsin cycle [7], [12], [13], we analyzed the effects of DADA on viral replication and trypsin expression in the lungs during the peak duration at days 2, 4 and 6 post-infection [7], [36], [37] and in other organs at day 4 post-infection [7], [13], [38]. Quantitative real-time PCR showed a significant reduction in the copy number of the viral non-structure protein 1 (NS-1) RNA gene segment in the lungs of infected mice treated with DADA at days 4 and 6 post-infection, compared with the vehicle-treated mice (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Several animal studies showed that host cellular trypsin-like proteases that activate viral fusion activity of hemagglutinin partially determine viral pathogenicity and infectivity 8 , 43 , 44 44 which can efficiently convert pro-MMP-9 to active MMP-9; 45 these both proteases can synergistically degrade the basement membrane proteins, including tight intercellular junctions and the blood–brain barrier 46 …”
Section: Pathophysiology Of Acute Influenza Infectionmentioning
confidence: 99%
“…In addition, a rare but often fatal encephalopathy caused by infection with a pneumotropic IAV has been reported in children with Reye's syndrome and influenza-associated encephalopathy (Delorme and Middleton 1979; Fujimoto et al, 1998). Recently, we reported that IAV infection can markedly upregulate latent pancreatic trypsin in the brain (Le et al, 2006) and various organs that may have not only a HA 0 processing activity but also a maturase activity of upregulated proMMP-9 (Yamada et al, 2006). …”
Section: Upregulation By Infection Of Latent Pancreatic Trypsin In Vamentioning
confidence: 99%